Capitalization of agricultural subsidies into land prices - Pavel Ciaian; Edoardo Baldoni; D'Artis Kancs; Dušan Drabik (Economics and Econometrics Research Institute (EERI), 2020)
We review the recent theoretical and empirical literature on the capitalization of agricultural subsidies into land prices. The theoretical literature predicts that agricultural subsidies are capitalized into land prices when land supply is inelastic and land markets function well. The share of capitalized subsidies significantly depends on the implementation of farm subsidies, local land-market institutions, rural market imperfections, and spatial effects. Most empirical studies have shown that agricultural subsidies are only partially capitalized into land prices, estimating that decoupled payments and land-based subsidies exhibit higher capitalization than coupled payments and non-land-based subsidies, respectively. However, estimated capitalization rates vary widely across studies largely because of data availability and identification challenges.
Keywords: O13; Q16; Q17; Q18; 330; agricultural subsidies; capitalization; land prices; land rents; land values; land market; coupled and decoupled payments